Scandinavian network for elite sport (2020)
The aim of the network between Section of Sport Science, Aarhus University, Department of Food and Nutrition, and Sport Science, University of Gothenburg, Norwegian School of Sport Sciences and Faculty of Sport and Health Science, University of Jyväskylä is to develop collaboration, knowledge exchange and research in the area of elite sport within Scandinavia.